SMART MULTI-STORED ROTARY CAR PARKING SYSTEM - MISS. PRAJAKTA RAMESH RAWAL; PROF. D. B. MANTRI (International Journal of Innovations in Engineering Research and Technology, 2021)
Today, we are living in advance country, where number of cars increasing day by day and the requirement of spaces for Parking those number of car is less. So space has become a very big problem and hence it’s become a very crucial necessity to avoid the wastage of space. Lack of space availability has always been a problem. The major cities are car parked callously on the streets. Hence, rotary car parking system could be one of alternative solution.In order to handle the issue of parking in busy places various types of vehicle parking systems are used worldwide namely Multi-level Automated Car Parking, Automated Car Parking System, and many more. This makes the system modernizedand evens a space-saving one. This idea is developed by using Atmega128 Microcontroller